CMET in triple-negative breast cancer: is it a therapeutic target for this subset of breast cancer patients?. (September 2014) - Gaule, Patricia B; Crown, John; O'Donovan, Norma; Duffy, Michael J
<x xml:space="preserve">Abstract</x> Introduction: The identification and validation of a targeted therapy for triple-negative breast cancer (TNBC) is currently one of the most urgent needs in breast cancer therapeutics. The cMET oncogene encodes a membrane-bound tyrosine kinase implicated in the formation and/or progression of several cancer types, including TNBC. Currently, inhibitors targeting cMET are undergoing clinical trials for a variety of cancers, including TNBC. These include anti-cMET and anti-hepatocyte growth factor (HGF) monoclonal antibodies and tyrosine kinase inhibitors. Areas covered: This article reviews the structure and mode of action of cMET, the role of cMET in cancer formation/development, with particular emphasis on its role in basal/TNBC and its potential as a therapeutic target for this subtype of breast cancer. Expert opinion: Due to cancer heterogeneity, it is unlikely that all TNBC patients will be responsive to anti-cMET drugs. Therefore, if cMET is to be used as a target for treatment, it will be important to identify predictive biomarkers to select, upfront, those patients likely to benefit. Potential predictive biomarkers for anti-cMET treatments in basal/TNBC include cMET, phospho-cMET, downstream signaling proteins or HGF. These putative predictive biomarkers should be evaluated in a large panel of basal/TNBC cell lines before incorporation into clinical trials involving anti-cMET drugs.